THE INFLUENCE OF PROFITABILITY AND STOCK PRICE INDEX MOVEMENTS IN THE AGRICULTURAL SECTOR ON THE INDONESIAN STOCK EXCHANGE (BEI) - Rusydi; Cut Dhea Fidela; Adinda Fayza; Farah Annisa; Cut Salsabila Putri (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
The movement of the price index for the agricultural sector over the last five years has been very volatile, and has had an impact on the performance of the agricultural sector, which ranks lowest compared to other sectors. This study aims to analyze the influence of profitability and stock price index movements in the agricultural sector on the Indonesian Stock Exchange (IDX). This study uses companies in the mining sector and the agricultural sector which are listed on the Indonesia Stock Exchange (IDX). The results of the study show that the variable profitability and price index are influential in the agricultural sector, because companies in the agricultural sector, especially in the sector, often export the products they issue, causing the value of the rupiah to increase continuously over time.